Inhibition of the IFN Response by Bluetongue Virus: The Story So Far - Rojas, José Manuel; Avia, Miguel; Martín, Verónica; Sevilla, Noemí (Frontiers in Microbiology, 2021)
Bluetongue virus (BTV) is the prototypical orbivirus that belongs to the reoviridae family. BTV infection produces a disease in ruminants, particularly in sheep, that results in economic losses through reduced productivity. BTV is transmitted by the bite of Culicoides midges and is nowadays distributed globally throughout subtropical and even temperate regions. As most viruses, BTV is susceptible to the IFN response, the first line of defense employed by the immune system to combat viral infections. In turn, BTV has evolved strategies to counter the IFN response and promote its replication. The present review we will revise the works describing how BTV interferes the IFN response.